Leadfield - French, Gerald L. (photographer):::Creator::::::::::::
Slide shows a sign for the ghost town of Leadfield. The sign reads: "Leadfield. This was a mining boom town founded on wild and distorted advertising. 300 hopeful people swarmed here and a post office was established in August, 1926. In February 1927, the post office closed and the town died."